2021
DOI: 10.30649/denta.v14i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Invitro Micro Encapsulation of Beta Tri Calcium Phosphate from Anadara granosa Shell Synthesis

Abstract: Background: Calcium is a material that is mostly contained in the Anadara-granose shell. Beta-TCP can be obtained from the hydrothermal process from the Anadara-granose shell. Beta-TCP has a chemical composition that approximates the structure of bones and teeth. Objective:The microencapsulation technique aims to increase stability, reduce side effects and toxic effects of drugs, and prolong the release of ingredients. The encapsulation process is an attempt to inhibit the dissolution speed of Calcium to preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Furthermore, calcium plays a role in fibroblast adhesion. 15,16,17 The results of Prananingrum's research in 2021 revealed that P. monodon, which has been subjected to deproteination, demineralization, depigmentation and deacetylation processes, can increase the formation of odontoblast-like cells in direct pulp capping treatment in experimental animal groups by giving chitosan for 7 and 28 days. It is due to the high degree of deacetylation used to manufacture direct pulp capping chitosan.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, calcium plays a role in fibroblast adhesion. 15,16,17 The results of Prananingrum's research in 2021 revealed that P. monodon, which has been subjected to deproteination, demineralization, depigmentation and deacetylation processes, can increase the formation of odontoblast-like cells in direct pulp capping treatment in experimental animal groups by giving chitosan for 7 and 28 days. It is due to the high degree of deacetylation used to manufacture direct pulp capping chitosan.…”
Section: Discussionmentioning
confidence: 99%